Pengaruh Aktivator HCL dalam Arang Tempurung Kelapa Guna Menurunkan Kadar COD, BOD, dan TSS pada Limbah Cair Tahu - Khuzaimah, Siti; Nafa, Kharismatun (JURNAL INTEGRASI, 2024)
Indonesia is an agricultural country where most of the population has a livelihood as farmers, especially in the Cilacap region of Central Java. Coconut plant (Cocus nucifera .L) is a tropical plant that thrives in Indonesia and is known by the public and has various uses. However, the utilization of coconut plants is generally only limited to the flesh of the fruit to be processed into coconut milk, so that other parts of the coconut plant, such as coconut shells tend to be potentially as waste and underutilized optimally[1]. Coconut shell can be used as activated charcoal using HCL activator with a simple and economical method. The number of activator concentrations used is 1N and 3N. By using the method of adsorption and filtration to treat wastewater tofu obtained a decrease in the levels of COD, BOD, and TSS are different. In the use of HCL activator 1N obtained results of reduction of COD, BOD, and TSS sequentially by 20%, 23%, and 73%. The results were obtained after the sample was adsorbed and filtration for 2 hours. While the effectiveness of the use of HCL 3N activator resulted in a decrease in COD, BOD, and TSS levels by 28%, 31%, and 76%.